FRASA NOMINA DALAM BAHASA MUNA DIALEK MA - Anita Rahayu; Rizal Rizal; FX Sawardi (Translation and Linguistics (Transling), 2024)
This research describes the behavior of grammatical functions in the X-bar theory in forming the FN structure of the Muna language, Mawasangka dialect. Apart from that, this research tries to find a formulation of the rules for the FN structure of the Muna language, Mawasangka dialect. Data collected from observations through informants who are native Muna speakers. Data was collected and compiled using descriptive methods. From the analysis results obtained, Muna language noun phrases can be combined with the noun phrase itself, but with the help of prepositions. In addition, noun phrases can consist of noun words as core projections combined with numeralia, adjectives, etc.